Research and development teacher education: authentic competency-based assessment - Sri-gran, Krapan; Homjan, Suchart; Wandee, Amorntheap (Institute of Advanced Engineering and Science, 2024)
This research aims to develop the development process of teachers and educational personnel for Competency-based assessment. The assessment based on the competency data collection used surveys, interviews, inquiries, observations, and quantitative data analysis by distributing frequencies, percentages, and averages. Results found that the current condition of teachers and educational personnel for the actual assessment was based on competencies. Overall, there was a high level. Moreover, the interview found that the management had promoted, supported, and advised teachers in applying concepts and techniques about actual assessment to evaluate learners. There were four processes in the research, and the results of the development process experiment found that the overall average of knowledge after use was higher than before using the process, and evaluating the process showed that the development of teachers was applicable, possible, accurate, and appropriate at a high level.